PENGGUNAAN MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN KREATIFITAS BERKARYA SENI RUPA PADA SISWA KELAS VIII SMPN 11 PADANG - ANA RAHMATILLAH, Dr. Ramalis Hakim, M.Pd. (Universitas Negeri Padang, 2019)
The purpose of this journal is to improve student creativity in SMP N 11 Padang. This research is a class action research using pretests and observation research design. The data usage techniques used are tests and observations. The results of paired simple test conducted in the research class shows the results of the Tcount Sig value is 0,000. Medium value of GIS used is α = 0.005. According to the test value T then the value of Sig Tcount 0.000 smaller than the table sig Tcount value of 0.005.Then H0 rejected and H1 accepted. Based on the explanation above, it can be concluded that the use of projecy based learning models to enhance children's creativity in art work in SMP N 11 Padang.Keywords: project based learning, creative work